ENGINEERING EDUCATION IN THE FIELD OF CIVIL ENGINEERING - Pavličić, Nevenka; Perazić, Mladen; Đurić-Jocić, Dragana; Knežević, Miloš (Journal of Applied Engineering Science, 2014)
Economic growth is of a crucial importance to the prosperity of a society and its members and such growth is based on a good quality and competent labour.  Educated and skilled human resources are one of the key factors to influence the positioning of a national economy in the international community. A properly regulated educational system and availability of education, as well as the "learning society" culture appear to be a generator of economic, cultural and general social progress.
Keywords: Employment Agency of Montenegro; Human recources; Civil engineering; Engineers; Education